2018
DOI: 10.1021/acsphotonics.8b00832
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Imaging through Fully-Flexible Glass-Air Disordered Fiber

Abstract: We demonstrate a fully flexible, artifact-free, and lensless fiber-based imaging system. For the first time, this system combines image reconstruction by a trained deep neural network with low-loss image transmission through disordered glass-air Anderson localized optical fiber. We experimentally demonstrate transmission of intensity images through meter-long disordered fiber with and without fiber bending. The system provides the unique property that the training performed within a straight fiber setup can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In particular, Karbasi, et al reported the first observation of TAL in disordered optical fibers [13][14][15]. The disordered optical fibers have since been used for high-quality image transport [22][23][24][25][26], beam multiplexing [27], wave-front shaping and sharp focusing [28][29][30], nonlocal nonlinearity [31,32], single-photon data packing [33], optical diagnostics [34], and random lasers [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Karbasi, et al reported the first observation of TAL in disordered optical fibers [13][14][15]. The disordered optical fibers have since been used for high-quality image transport [22][23][24][25][26], beam multiplexing [27], wave-front shaping and sharp focusing [28][29][30], nonlocal nonlinearity [31,32], single-photon data packing [33], optical diagnostics [34], and random lasers [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The fast inference and the ability of learning a versatile mapping from measurement to signal contribute to the wide adoption of neural networks in recent years [16]- [20]. Most of these approaches use a neural network with parameters θ to approximate the inverse mapping A inv (g) based on a series of observations {f i }.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deep learning has been used in optical communications [58,59], and more specifically, for real-time fibre mode demodulation [60], end-to-end fibre communications [61], and improvement in fibre transmission [62]. Imaging has also been demonstrated using microstructured fibre [63] and multimode fibre array [64] with deep learning.…”
Section: Introductionmentioning
confidence: 99%